Bridging Vocational Students’ Needs and Industry Demands: Designing Authentic English Learning Materials for Hotel Services - Alhusna, Asma; Suparmi, Suparmi (Journal of English Education and Teaching, 2025)
The hotel industry’s demands on graduates from the hotel department in vocational school are high. However, graduates’ communication skills using English are still low because imbalance between English learning materials and workplace realities. This study aims to identify the needs of authentic English learning materials that align with industry language expectations. This explanatory sequential mixed-method design involved 62 hotel department students, 5 English teachers, and five hotel stakeholders in Padang, Indonesia. Questionnaires, interview guidelines, and focus group discussions (FGDs) were used to gather the quantitative and qualitative data. The quantitative data were analyzed using descriptive statistics, while the thematic analysis was used for qualitative data. The results of this study indicate that both oral (e.g., greeting guests, managing complaints, and handling reservations) and written communication (e.g., confirmation emails and service reports) were highly prioritized for the hotel industry. Additionally, the vital authentic resources needed to be learned by students included reservation forms, brochures, guest service videos, and business emails. These findings highlight that teachers need to foster student engagement and professional competence by shifting from textbook-based to real-task-driven approaches to teach English in the hotel department of vocational schools.